«Vado all’Aula magna dell’Università di Roma». Premesse agli “Incontri di ricerca psichiatrica” 2003-2005 - Fagioli, Massimo (Il sogno della farfalla, 2025)
This monographic issue collects the introductory premises written by the psychiatrist M. Fagioli for the Psychiatric Research Meetings held between 2003 and 2005 at Sapienza University of Rome. These meetings, the result of a collective elaboration, were meticulously and originally orchestrated by Fagioli, who sought to achieve an absolute fusion of image and content. In these texts, the psychiatrist of Collective Analysis reflects on the diversity of his own mental reality in different contexts: when interpreting in group psychotherapy, when delivering university lectures, and when attending the meetings as an audience member. However, these premises also serve as an opportunity to delve deeper into his personal research journey and the history of Collective Analysis, as well as to investigate some fundamental themes of his theory. These pages revisit reflections on dream interpretation, the concepts of movement and transformation, and the precise meaning of terms such as narcissism and identification, in that relentless effort to «give a name to the things» of the human mind.